Respuesta :
Now that we have both of these zero terms, we can multiply them to get a standard form.
f(x) = (x - 6)(x + 4)
And while this will give us the zeros we need, it will no give us the lead coefficient. So we must multiply by the desired lead coefficient.
f(x) = 5(x - 6)(x + 4)
f(x) = 5(x^2 - 6x + 4x - 24)
f(x) = 5(x^2 - 2x - 24)
f(x) = 5x^2 - 10x - 120
f(x) = (x - 6)(x + 4)
And while this will give us the zeros we need, it will no give us the lead coefficient. So we must multiply by the desired lead coefficient.
f(x) = 5(x - 6)(x + 4)
f(x) = 5(x^2 - 6x + 4x - 24)
f(x) = 5(x^2 - 2x - 24)
f(x) = 5x^2 - 10x - 120
Answer:
1x^2-sqrt(3)b+1/2=0 or
2x^2 - 2sqrt(3)b+1=0
Step-by-step explanation:
ax^2 +bx+c=0
a=1, b,c=?
x1=(sqrt(3)-1)/2
x2=(sqrt(3)+1)/2
x1+x2=-b/a
x1 *x2 =c/a
x1 +x2=
(sqrt(3)-1)/2+(sqrt(3)+1)/2=
2sqrt(3)/2=
sqrt(3)=-b/1
b=-sqrt(3)
x1*x2 =
((sqrt(3)-1)/2) *((sqrt(3)+1)/2) =
((sqrt(3))^2 - 1^2) /4=
(3-1)/4=
2/4=
1/2=c/1
c=1/2
ax^2 +bx+c=0
1x^2-sqrt(3)b+1/2=0 /*2
2x^2 - 2sqrt(3)b+1=0